Partisipasi Perempuan Terhadap Pengambilan Keputusan Dalam Penyelenggaraan Pemerintah Daerah yang Demokratis - Inna Junaenah (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2014)
Abstract: Decision Against Women's Participation In The Democratic local government management. There have been many studies and settings on the relation of women to decision-making in a government organization. It also encouraged the International in 1995 in the World Women's Conference in Beijing fourth, which resulted in a recommendation by the mention of the Beijing Platform for Action. This declaration has prompted action plans in various countries, including in Indonesia, including to target the achievement of women's representation in Parliament 33.3 percent. Such a declaration of some of the ways that women can participate in decision making. The position of women in parliament is believed to affect directly to influence the established law. Abstrak: Partisipasi Perempuan Terhadap Pengambilan Keputusan DalamPenyelenggaraan Pemerintah Daerah Yang Demokratis. Telah banyak kajian danpengaturan mengenai relasi perempuan dengan pengambilan keputusan dalam suatu penyelenggaraan pemerintahan. Hal itu didorong pula secara Internasionalpada tahun 1995 dalam Konferensi Perempuan se-Dunia keempat di Beijing,yang menghasilkan rekomendasi dengan penyebutan Beijing Platform for Action.Deklarasi ini telah mendorong rencana aksi di berbagai negara, termasuk di Indonesia, di antaranya untuk menargetkan pencapaian keterwakilan perempuan di Parlemen 33,3 persen. Pencanangan yang demikian merupakan sebagian carasupaya perempuan dapat turut serta dalam pengambilan keputusan. Posisi perempuan di parlemen diyakini berpengaruh secara langsung untukmempengaruhi hukum yang dibentuk. DOI: 10.15408/jch.v1i2.1465